Analysis of the Quality of Human Resources of Mustahik Assisted by the National Amil Zakat Agency of Mataram City - Dita Marfinia; Busaini, Busaini (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
This study investigates the collection of zakat in Indonesia through the National Amil Zakat Agency (BAZNAS) with a focus on analyzing the quality of human resources of mustahik assisted by the National Amil Zakat Agency of Mataram City. BAZNAS collaborates with the Ministry of Social Affairs to improve the welfare of mustahik through the integration of poverty data. Qualitative research methods are used to describe the quality of Human Resources (HR) of mustahik BAZNAS Mataram City. The descriptive qualitative research design leads to data collection through observation, interviews, and documentation at the location of the Mustahik Development program. Data validity is assessed through triangulation of data sources and theories. The results showed that zakat funds were channeled through training and business capital to mustahik human resources, with the cooperation of BLK to improve skills. The impact of coaching is seen in the improvement of the ability and economic independence of mustahik HR. However, obstacles arise in changing the mindset of mustahik human resources related to dependence on assistance. Although coaching provides experience and skills, the lack of education is an obstacle in achieving the goal of Baznas Mataram City to improve the quality of mustahik human resources.